(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Reformed Christianity is one of the Protestant denominational branches in Indonesia. The Reformed tradition exhibits distinct theological and liturgical characteristics compared to other Christian denominations. Consequently, architectural design must accommodate Reformed theological concepts while supporting its liturgical practices and doctrinal views. Although Reformed churches share a unified theological belief, their architectural forms vary significantly, influencing the sacred atmosphere within these spaces. In 2024, the Gereja Reformed Injili Indonesia (GRII) in Bandung inaugurated a new church building. Preliminary observations indicate that this church’s architectural design diverges from typical Reformed churches, impacting the spatial ambiance. This study focuses on the relationship between the sacred atmosphere and the architectural design of Reformed churches, specifically examining the new GRII Bandung church. The research investigates the connection between the sacred ambiance and the architectural design of the GRII Bandung church. It seeks to provide insights for the academic community, contributing to theories and concepts related to church architecture in general and Reformed church architecture in particular. The findings are anticipated to offer alternative design approaches for Reformed churches and provide valuable input for church management policies. Ultimately, this study aims to lay the groundwork for more comprehensive future research in this area.